2-Substituted-isoindoles: a novel synthetic route and a study of the Diels–Alder and Michael reactions. (1st November 2011) - Voitenko, Zoia; Sypchenko, Volodymyr; Levkov, Igor; Potikha, Lyudmila; Kovtunenko, Volodymyr; Shishkin, Oleg; Shishkina, Svetlana
A novel one-step procedure for the synthesis of 2-substituted-isoindoles and 1-aryl-2-substituted-isoindoles is described. The procedure is based on the reaction of 2-(bromomethyl)benzaldehyde or 2-(bromomethyl)benzophenone derivatives with primary aromatic or aliphatic amines. Reactions of 1, 2-diarylisoindoles with N-phenylmaleimide were studied. Refluxing the reactants in i-PrOH in the presence of triethylamine leads to the formation of Diels–Alder endo-adducts; whilst refluxing in AcOH in the presence of AcONa affords Michael adducts. The structure of the latter was confirmed by X-ray diffraction.